Investigated Study of Close Range Photogrammetry for High Precision Measurement - Waisurasingha, Chatticahi (Engineering and Applied Science Research, 2013)
High precision measurement system is very important for industrial line production, molding design part and quality control part. Normally, for high precision measurement, this system uses a Digital Laser Scanner to scan the surface of an interested object. But this method is very expensive in order to get the high precision for this measuring system. So, we need to look for another method that can offer or produce the same precision as this system and cheaper than this system in order to support Thai Small and Medium Enterprises (SME) Industrial production which now has been fully supported by Thai Government. The experiment output indicates the produce results of all case studies that the accuracy obtained usual not greater than 80 micron measured by close range digital photogrammetric. The main features of successful case studies are: number of camera exposure stations. Type of camera calibrations, type of control and tie points marking, accuracy of control points, type of control, type of targets and lighting environment control.